HUBUNGAN KOMUNIKASI EFEKTIF DENGAN MUTU PELAYANAN KESEHATAN DI RUMAH SAKIT - Marline M Mamesah; Roberto A. Geonarso; Afif Kurniawan; Silvia Haniwijaya (Journal of Hospital Administration and Management, 2020)
Hospital is one of the health service institutions that has responsibility to improve health status of community. Changes in disease patterns, demographic structures, science and technology, and economy affect people's expectations of quality services. Service recipient satisfaction will be achieved if the service is in accordance with what is needed and expected. This study was conducted in one hospital in Surabaya using a cross sectional with 30 patients aged 25-40 years as respondents. A total of 46.7% of respondents stated that health workers had communicated effectively, and 58% were satisfied with the quality of service. The results showed the relationship between communication and service quality (P=0.001). Communication is one of the most important things to help patients understand their health situation, problems and treatment plans. Good communication can contribute to building trust between patients and health workers. Quality is the overall characteristics and description of a product or service that shows its ability to satisfy customer needs. Good effective communication will improve the quality of good service so that patients feel satisfied with the services provided by health workers. Keywords : quality, service, communication, satisfaction